The use of gamification in knowledge management processes: a systematic literature review - Sampaio, M. C, (2020)
Purpose: The purpose of this article is to present a systematic literature review that synthesizes the investigations made into the use of Gamification in Knowledge Management processes in recent years, and a conceptual model for analysis of the Gamification of Knowledge Management Systems. Theories: Since the last decade the Gamification - defined by the application of game design principles in a non-game context - as a management practice has become increasingly challenging for researchers. At the height of the Knowledge Age, in which we live today, knowledge and the organizational capacity to create, disseminate and retain it is one of the most important sources of competitive advantage for organizations. As employees’ knowledge is critical for companies, it is essential to find effective mechanisms to encourage collaborators to share knowledge. In this field, gamification is a dynamic to be considered as an enabler of successful knowledge management systems. Methodology: A systematic review of the literature was carried out, analyzing the scientific articles obtained through electronic databases, manual research and the cross-referencing of bibliographic references to identify and synthesize studies on the use of gamification in Knowledge Management processes in the period from 2015 to 2018. Results: This study demonstrates that the use of gamification in knowledge management processes has a positive impact on employees’ motivation and involvement with these systems, while promoting the creation, transfer and sharing of knowledge in the organization. A conceptual model for the gamification of knowledge management systems is proposed, intended to be a valid contribution to the operationalization of future studies on the link between gamification and knowledge management.